ASSA14-03-45 Selective late sodium current inhibitor altered atrial electrical conduction but not atrial activation pattern. (1st December 2014) - Sihui, H; Qiaomei, Y; Lin, W
Abstract : Objective: Rhythm control is an important strategy to treat atrial fibrillation (AF). However, drugs currently used for rhythm control are neither sufficiently safe nor effective. Ranolazine (Ran) and dronedarone (Drone) are new drugs with efficacy to maintain sinus rhythm. Ran, a late sodium current inhibitor, but not Drone, caused no increase in mortality in patients with AF and organic heart disease. The objective of this study was to compare the effect of ranolazine and dronedarone on atrial activation pattern and interatrial conduction. Method: Electrogram was recorded from two identical multielectrode recording arrays (48 channels each) placed against the left and right atria of Langendorff-perfused female rabbit isolated hearts. Continuous 5 s recordings were analysed offline. Isochronal maps were drawn from the recording data. Data were analysed with Prism version 5 and expressed as mean ± SEM. To compare values of measurements obtained from the same heart before and after a drug treatment, repeated measures one-way analysis of variance (ANOVA) was used to determine which pairs of group means was significantly different. Results: Ran (1–30 μm) significantly prolonged intra-atrial activation conduction time and mean activation time in frequency- and concentration-dependent manners. At the frequency of 3.3 Hz, 4.0 Hz and 5.0 Hz, Ran (1–30 μm) increased left and right intraatrial conduction time by 5.22 ± 0.14, 7.33 ± 0.07, 9.78 ± 0.02 ms, and 6.89 ± 0.09, 8.83 ± 0.23 and 13.06 ± 0.96 ms, respectively. It also prolonged left and right atrial mean activation time by 2.85 ± 0.03, 3.92 ± 0.11, 5.23 ± 0.09 ms and 3.15 ± 0.14, 3.75 ± 0.15, 6.58 ± 0.40 ms, respectively (n = 9, p < 0.05). Ran caused no change in the activation pattern of the inter-atrial conduction. In contrast, Dron (0.1–3 μm) caused no significant changes in atrial activation conduction time and mean activation time (n = 7, p > 0.05). Conclusion: Compared with multichannel inhibitor dronedarone, selective late sodium current inhibitor ranolazine has obvious frequency dependence to slow the intra-atrial electrical conduction, which can partially explain the anti-AF mechanism of ranolazine.